An efficient DFT method of predicting the one-, two- and three-bond indirect spin–spin coupling constants involving a fluorine nucleus in fluoroalkanes. Issue 86 (1st September 2016) - Gryff-Keller, Adam; Szczeciński, Przemysław
Abstract : The values of the indirect nuclear spin–spin coupling constants for a series of aliphatic fluorocompounds have been calculated using DFT-based methods and compared with the experimental values of these parameters. Abstract : The values of the indirect nuclear spin–spin coupling constants for a series of aliphatic fluorocompounds have been calculated using DFT-based methods and compared with the experimental values of these parameters. The set of the molecular objects contained four fluoromethanes, five fluoroethanes, two fluorocyclopropanes, and eleven fluorocompounds containing either five-membered or six-membered rings. The effectiveness of three hybrid functionals, B3LYP, PBE0 and BHandH and three basis sets, 6-311++G(2d, p) (s), 6-311++G(3df, 3pd) (m) and aug-pcJ-3-2006 (l) has been checked. In order to compare the results concerning various types of coupling constants and obtained by various methods, a prediction-quality criterion has been proposed. It has been found that only the BHandH functional ensures calculating the proper values of one-bond fluorine–carbon and two-bond fluorine–fluorine coupling constants. For this functional application of the s basis, the smallest of the bases tested, has already yielded acceptable good results. The DFT BHandH/s PCM method has also provided the proper values of n J (F, H) ( n = 1, 2, 3) and n J (F, C) ( n = 2, 3) parameters. On the other hand, the analysis of the limited number of the results concerning 1 J (C, H) coupling constants has pointed out that in this case this method is less effective than the DFT PBE0/l PCM method.